The Influence of Kades’s Leadership Style Toward the Land and Building Tax (L and B Tax) Payment According to Equity Theory Perspective Versus Maslow Theory in Mataraman Javanese Society - Prastiwi, Dewi; ., Aisyaturrahmi; Arieftiara, Dianwicaksih (International Journal of Engineering and Technology, 2019)
The research aims to prove empirically the influence of Kades/kadesâ€™s leadership style to the L and B Tax payment obedience to the Mataraman Javanese society distinguished by its characteristic in being loyal to the leader. This research approaches quantitatively by using the primary data in the form of questionnaire directly spread to the respondents in 15 districts of Madiun. The result of the research shows that there are the influence between the kadesâ€™s leadership style assessment and the the L and B tax payment obedience. Based on the alternative test result, democratic and autocratic leadership styles have big influences in the obedience of L and B tax payment, meanwhile the participatory and delegative leadership styles do not. It confirms the Equity Theory where individual will always assess the received input and output equity. On the other hand, in accordance of Maslowâ€™s Theory, the society which is on the physiological need stage tends to accept the autocratic leadership style since they remain to have no sufficient motivation to fulfill the social needs.Â